UPAYA DIPLOMASI INDONESIA TERHADAP AUSTRALIA UNTUK MENANGGAPI KEBIJAKAN TOBACCO PLAIN PACKAGING ACT 2011 PERIODE 2012 - 2017 - Bagus Putra Laksana, - (2019)
Tobacco processing industry is one of industry that contributes significantly to state revenues where in 2012 it was challenged by Tobacco Plain Packaging Act 2011 enactment as an effort to reduce tobacco products demand. The purpose of this study was to analyze Indonesian government diplomacy efforts on Australia to response Tobacco Plain Packaging policy. Qualitative approach is used as a research method. Data collection techniques use literature studies. Economic diplomacy and economic diplomacy models are used as a main theory. The results showed that Indonesian government diplomacy efforts were motivated by the Indonesia's national interests in the tobacco processing industry which contributed significantly to state revenues. The diplomacy efforts carried out by the Indonesian government are economic diplomacy by optimizing bilateral forums. Economic diplomacy model that has been developed were still categorized as a traditional type where the ministry of trade functions as the main spearhead of Indonesian economic diplomacy and has not been effective because it's still characterized by strong sectoral ego and weak coordination among agencies which are marked by differences in attitude between the ministry of health and ministries of trade related to the FCTC which can actually weaken the government's economic diplomacy process related to Tobacco Plain Packaging Act 2011. Economic diplomacy efforts through bilateral forums failed, finally the government took legal steps to submit dispute settlement to WTO. This effort isn't effective also because there is no counter narrative to fight against scientific research conducted by Australia that with plain packaging will be more effective in reducing the number of cigarettes demands